2011
DOI: 10.1002/dc.21599
|View full text |Cite
|
Sign up to set email alerts
|

Malignant effusion of chromophobe renal‐cell carcinoma: Cytological and immunohistochemical findings

Abstract: Malignant effusions because of renal-cell carcinoma (RCC) are an unusual event and occur in patients with papillary and clear cell tumors. We have studied a 65-year-old man who underwent right renal tumorectomy, diagnosed as chromophobe RCC (pT1). After 16 months, the patient presented cough and fever. Positron emission computed tomography demonstrated extensive mediastinal lymphadenopathy. Chest radiograph showed right pleural effusion. The cytological examination of the fluid showed malignant cells. Immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Notably, pain requiring removal of catheter was seen only in 0.4% of cases. [5][6][7] In our opinion, predisposing factors include decreased muscle mass and a poor nutritional status with a low albumin level that slows healing and decreases scar formation, which is essential for the catheter to stay in place. 10 When complete drainage occurs, the pleural layers repose each other and the catheter occasionally causes pain.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, pain requiring removal of catheter was seen only in 0.4% of cases. [5][6][7] In our opinion, predisposing factors include decreased muscle mass and a poor nutritional status with a low albumin level that slows healing and decreases scar formation, which is essential for the catheter to stay in place. 10 When complete drainage occurs, the pleural layers repose each other and the catheter occasionally causes pain.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of special cases of malignant effusion secondary to RCC.As an example; Chetcuti K et al reported a case of massive spontaneous hemothorax in a 78 year-old man with a history of RCC. The culprit was a chest wall metastasis of RCC (Chetcuti et al, 2010;Teresa et al, 2011).…”
Section: Pulmonary Manifestationsmentioning
confidence: 99%
“…The most common tumors for c-kit-positive immunostaining are gastrointestinal stromal tumors. Other tumors showing c-kit positivity are melanocytic lesions, testicular seminoma, chromophobe renal cell carcinoma, renal oncocytoma, cholangiocellular carcinoma, hepatocellular carcinoma, carcinoma showing thymus-like elements, osteosarcoma, pancreatic endocrine tumor, neuroendocrine carcinoma of the uterine cervix, and endometrial and ovarian carcinoma [2,3,4,5,6,7,8,9,10,11,12,13]. Carcinoembryonic antigen (CEA) has been reported in a large number of carcinomas, particularly in adenocarcinomas of the gastrointestinal tract and lung.…”
Section: Introductionmentioning
confidence: 99%